Implementasi SNA dalam Menilai Popularitas Platform Pemesanan Makanan Online Berbasis Percakapan Twitter - Adriyansyah Juri Setyo Wibowo; Setyawan Wibisono (Sekawan Institut, 2024)
This research aims to understand the popularity of online food ordering platforms in Indonesia, although the data taken in Indonesian includes allied languages. This research combines the SWARA, WASPAS, and Social Network Analysis (SNA) approaches to achieve its objectives. The problem formulation proposed is how to measure and analyze the popularity of online food ordering platforms based on interaction data on Twitter social media. The SWARA method is used to determine the weight of the evaluation criteria, while WASPAS is applied to rank online food ordering platforms. Meanwhile, SNA is applied to analyze interaction patterns and user preferences for various online food ordering platforms. Twitter was chosen as the main data source because it provides direct conversation data and real depictions, allowing for in-depth and accurate analysis. Through Twitter, research can capture the dynamics of user interactions and how they communicate about various online food ordering platforms. This research aims to provide a strong foundation for decision makers in designing more effective marketing strategies and provide insight into the dynamics of competition in the online food ordering platform industry. The research results show that SNA-based analysis is able to clearly identify interaction patterns and user preferences.